Risk Management of School Administrators under Songkhla Primary Educational Service Area Office 3 in Covid-19 Situation - Srisuwanno, Wasan; Kongchuay, Rujirapun (Princess of Naradhiwas University Journal of Humanities and Social Sciences, 2023)
The objectives of this research were 1) To study the risk management of educational institution administrators under Songkhla Primary Educational Service Area Office 3 in COVID-19 situation. 2) To compare the risk management of educational institution administrators in COVID-19 situation according to the teachers’ opinion classified by academic level, work experience, and the size of the educational institution. 3) To study the risk management recommendations of the educational institution administrators under Songkhla Primary Educational Service Area Office 3 in COVID-19 situation. This research is a survey research and there were 338 teachers under Songkhla Primary Educational Service Area Office 3, selected by using stratified sampling of the school size. The research instrument was a 5-level estimation scale questionnaire with a reliability value of 0.96. The statistics used in the data analysis were frequency, percentage, standard deviation, t-test, and One-Way ANOVA. The results of the research were found that; 1) The overall and each aspect of risk management of school administrators under Songkhla Primary Educational Service Area Office 3 in COVID-19 situation was at a high level. 2) The comparison of risk management of school administrators under Songkhla Primary Educational Service Area Office 3 in COVID-19 situation, according to the opinions of teachers with different educational backgrounds and working experiences in which the overall result was found to be quite the same except the financial risk which was discovered to be statistically significant different at the level of .05. According to the size of different educational institutions, the overall/each aspect was yielded to be different at statistically significant level of .001. and 3) Recommendations for risk management of educational institution administrators under Songkhla Primary Educational Service Area Office 3 in the situation of COVID-19, based on the teachers’ perspectives were found that the school administrators should review the strategic plan every academic year in order to encourage teachers in developing instructional management that is appropriate for the situation, and support in making lesson plans and projects that are in accordance with the situation. Moreover, the school administrators should establish operational guidelines and agreement with teachers within the educational institution.